ORIGIN OF WATER IN THE MUTNOVSKY GEOTHERMAL FIELD: AN OXYGEN (18O) AND HYDROGEN (D) STUDY - Kiryukhin A.V.; Takahashi M.; Polyakov A.Yu.; Lesnykh M.D.; Bataeva O.P. (My University, 1999)
Isotopic analyses of fluids from the wells drilled in the Mutnovsky geothermal field revealed that the water of a melting glacier in the crater of Mutnovsky Volcano might be a source of water supply to the Dachnyi and Verkhne-Mutnovsky reservoirs of the geothermal field.